Zakhar Prilepin: a Literary Portrait - Borkowska, Aldona (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
Since his debut in 2004, Zakhar Prilepin has constantly been present on the Russian cultural scene. A literary scholar, journalist, writer, politician and even a military man, he is the author of a set of highly popular and emblematic novels which portray Russia at the turn of the 21st century. The writer has won many significant Russian literary awards and attracted the attention of both literary critics and the general audience. In the paper, a literary portrait of Zakhar Prilepin is sketched and the reasons for the writer’s popularity are investigated.